An Investigation into English as a Foreign Language Textbooks in Vocational and Technical Schools - Hossein Salarian (PT. Pusmedia Group Indonesia, 2025)
Certainly, needs analysis is to determine the target language learning or teaching needs for developing a valid and useful curriculum. In identifying the special needs of learners, we face with the term “need analysis”, which have had diverse connotations. Moreover, close integration of language and the particular context for specific students is of prime importance for adapting and adopting English textbook. To this end, this paper briefly scrutinizes the needs analysis of English learning from students’ perceptions and teachers’ expectations. Therefore, two separate questionnaires were administered to 200 students and 30 teachers at 10 vocational and technical schools from three provinces in Iran and the resulting data were investigated through t-test. For determining any significant difference between the perceptions and expectation of the two groups Chi-square test was used. The results showed that students and teachers had various viewpoints of English learning needs. In addition, the skills used in these schools do not totally match with students’ competence and with their careers in future. Like other high schools’ English textbooks, the existing textbooks for vocational and technical schools in Iran are academically-oriented with more emphasis on cognitive development and less consideration to students’ needs, abilities, interests, potentials and developmental history. Therefore, the findings emphasizes the necessity of developing and producing English textbooks in terms of students’ language levels, competence, needs, and the objectives of the program in these schools. If English textbooks are designed and developed well regarding materials and learners’ factors, then vocational /technical curriculum will provide a good basis for learning and teaching. The study has recommendations and implications for improvement of English for specific purpose courses considering these students’ needs.